Fullerenes and their cross-linking in organic and perovskite solar cells - Ramirez, I (2017)
This thesis is concerned with the photo-dimerisation mechanism of C60 in bulk hetero-junction (BHJ) organic solar cells, its effect on device performance and the use of cross-linked fullerenes as electron selective layers (ESL) for perovskite solar cells. The photo-dimerisation of fullerenes has recently been identified as negatively impacting the stability of BHJs but the process is incompletely understood in BHJs. By employing model systems, we independently study the effects of donor (D) energetics and morphology. We find that for donors forming charge transfer (CT) states much lower in energy than the lowest energy C60 excitons, the dimerisation is suppressed at only 5% D loading. This is in contrast to Ds forming CT states with energies comparable to C60 excitons, for which dimerisation is suppressed from 20% donor loading. It is also found that the electron affnity (EA) increases by 100 meV after dimerization but that CT states remain unaffected. These observations are combined into a complete model of dimerisation in BHJs. It is concluded that avoiding dimerisation requires either low D band-gaps, a deliberate energy loss or low electron mobilities. Thus the effect of dimerisation on devices is revisited. From our knowledge of which systems do and do not dimerise and temporal arguments, losses in performance induced by dimerisation and other extrinsic effects are de-convoluted. Surprisingly no significant degradation is found to originate from dimerization. By contrast, we observe sever performance losses similar to those previously attributed to dimerisation, which we suggested to be caused by the MoO3 hole transport layer, which is commonly employed in OPV. Lastly we address the problem of C60 dissolution upon perovskite deposition from solution. To avoid dissolution, two cross-linkable fullerenes are introduced as ESLs. Both display good morphological and electronic characteristics and resulted in greatly improved photo-voltaic performance compared to C60. This is attributed to the avoided dissolution, which because of a likely reduction in pin-holes and inhomogeneities, suppresses surface recombination with the FTO electrode.